Co-delivery of doxorubicin and interleukin-2 via chitosan based nanoparticles for enhanced antitumor efficacy. (1st January 2017) - Wu, Jingjing; Tang, Cui; Yin, Chunhua
Graphical abstract: Abstract: In order to reduce toxicity and improve antitumor therapeutic effects of doxorubicin (DOX) and recombinant human interleukin-2 (rhIL-2), we developed a hydrophilic cationic polymer (N, N, N-trimethyl chitosan, TMC) based nanocomplexes (FTCD/rhIL-2) which could efficiently mediate systemic co-delivery of hydrophobic DOX and water-soluble rhIL-2 to achieve the purpose of combination therapy. DOX was covalently conjugated to TMC through cis -aconitic anhydride (CA) which endowed nanocomplexes a pH-sensitive release of DOX, while rhIL-2 was loaded through electrostatic adsorption without compromise of bioactivity. The resultant nanocomplexes exhibited sub-spherical shape (∼200 nm) and positive charge (>20 mV). Folate (FA) modification was utilized with the intention of active targeting, which was however correlated with weakened tumor growth inhibition, emphasizing the importance of balance in overcoming diverse delivery barriers for efficacious antitumor therapy. Compared with free drugs, FTCD/rhIL-2 nanocomplexes significantly delayed tumor growth, increased the serum immunoglobulin G (IgG) level and the amount of tumor infiltrated cytotoxic T lymphocytes. These results indicated that the combinational administration of DOX and rhIL-2 based on polymer nanoparticles could serve as an effective strategy in antitumor therapy. Statement of Significance: Combined administration of doxorubicin (DOX) and recombinant human interleukin-2 (rhIL-2) has been utilized for the treatment of tumors. However the traditional administration brought to severe side effects, and the efficiency of current delivery systems were unsatisfactory. Herein we developed a hydrophilic cationic polymer based nanoparticle delivery system which facilitated simultaneous and systemic co-delivery of hydrophobic DOX and water-soluble rhIL-2. This system achieved pH-sensitive release of DOX and sustained release of rhIL-2 in vitro, meanwhile, improved anti-tumor efficacy and reduced side-effect in vivo . Thus, our study provided a solution for combinational administration of DOX and rhIL-2 and could serve as an effective strategy in antitumor therapy.